Draft Genome Sequence of Stenotrophomonas maltophilia Strain B418, a Promising Agent for Biocontrol of Plant Pathogens and Root-Knot Nematode - Wu, Yuanzheng (Genome Announc, 2015)
Stenotrophomonas maltophilia strain B418 was isolated from a barley rhizosphere in China. This bacterium exhibits broad-spectrum inhibitory activities against plant pathogens and root-knot nematode along with growth-promoting effects. Here, we present the draft genome sequence of S. maltophilia B418.